Comparison of free and total 25-hydroxyvitamin D in normal human pregnancy - Tsuprykov, Oleg; Hocher, Berthold (The journal of steroid biochemistry and molecular biology, 2019)
Vitamin D status correct monitoring during pregnancy is critically important for both maternal and fetal health. 25-Hydroxyvitamin D (25(OH)D) - a prohormone of a biologically active 1,25-dihydroxyvitamin D (1,25(OH)2D), despite the lack of biological activity, during the past decades has been routinely used as a main biomarker characterizing vitamin D status. About 85% of 25(OH)D in the bloodstream is bound to its specific carrier - vitamin D-binding protein (DBP), the remaining 15% are loosely bound to albumin, and only less than 0.1% are free in the circulation (“free 25(OH)D”). Total 25(OH)D is the sum of DBP-bound, albumin-bound and free 25(OH)D. According to a “free hormone hypothesis”, only free 25(OH)D is able to induce a biological effect. Normal pregnancy is characterized by elevated serum DBP levels, and due to this fact the diagnostic strength of serum total 25(OH)D has been questioned. Free 25(OH)D might be a better characteristic of vitamin D status in this settings. We aimed to compare the diagnostic strength of a routine total 25(OH)D with directly measured free 25(OH)D in normal pregnancy by comparing the association strength between free and total 25(OH)D with biomarkers of bone health (PTH, calcium, bone-specific alkaline phosphatase (BSAP)), lipid metabolism (adiponectin, LDL, HDL), kidney function (urea), endocrine parameters (T4, T3, TSH), and group B water-soluble vitamins. The study was conducted in 368 healthy white pregnant women - residents of north-east Germany. Free 25(OH)D showed an overall better associations with gestational age, markers of bone metabolism (calcium (rho = 0.141, p = 0.007 with free 25(OH)D; rho = 0.060, p = 0.251 with total 25(OH)D) and BSAP (rho = −0.203, p < 0.001 with free 25(OH)D; rho = −0.108, p = 0.038 with total 25(OH)D), lipid metabolism parameters (adiponectin (rho = 0.142, p = 0.008 with free 25(OH)D; rho = 0.054, p = 0.307 with total 25(OH)D), LDL cholesterol (rho = −0.191, p < 0.001 with free 25(OH)D; rho = 0.033, p = 0.539 with total 25(OH)D)) and a kidney function marker (urea (rho = 0.114, p = 0.032 with free 25(OH)D; rho = 0.008, p = 0.887 with total 25(OH)D)) than total 25(OH)D. In conclusion, the current study revealed that free 25(OH)D is a more precise determinant of the vitamin D status during normal human pregnancy than total 25(OH)D. In the settings of normal pregnancy, free 25(OH)D revealed better associations with markers of bone metabolism (calcium, BSAP), lipid metabolism (adiponectin, LDL cholesterol, LDL/HDL ratio) and kidney function (urea) than total 25(OH)D.
Gesehen am 12.09.2019